Lack of understanding of acute HIV infection among newly-infected persons-implications for prevention and public health: The NIMH Multisite Acute HIV Infection Study: II. - Remien, Robert H; Higgins, Jenny A; Correale, Jackie; Bauermeister, Jose; Dubrow, Robert; Bradley, Mark; Steward, Wayne T; Seal, David W; Sikkema, Kathleen J; Kerndt, Peter R; Mayer, Kenneth H; Truong, Hong-Ha M; et al. (AIDS and behavior, 2009)
Acute/early HIV infection is a period of high HIV transmission. Consequently, early detection of HIV infection and targeted HIV prevention could prevent a significant proportion of new transmissions. As part of an NIMH-funded multisite study, we used in-depth interviews to explore understandings of acute HIV infection (AHI) among 34 individuals diagnosed with acute/early HIV infection in six US cities. We found a marked lack of awareness of AHI-related acute retroviral symptoms and a lack of clarity about AHI testing methods. Most participants knew little about the meaning and/or consequences of AHI, particularly that it is a period of elevated infectiousness. Over time and after the acute stage of infection, many participants acquired understanding of AHI from varied sources, including the Internet, HIV-infected friends, and health clinic employees. There is a need to promote targeted education about AHI to reduce the rapid spread of HIV associated with acute/early infection within communities at risk for HIV.
Keywords: Acute Disease; AIDS Serodiagnosis; Awareness; Health Knowledge, Attitudes, Practice; HIV Infections; HIV-1; Humans; Male; National Institute of Mental Health (U.S.); Questionnaires; Risk Factors; United States; Young Adult